2012
DOI: 10.1093/jac/dks271
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and echinocandin susceptibility of Candida parapsilosis sensu lato species isolated from bloodstream infections at a Spanish university hospital

Abstract: Echinocandin drug susceptibility testing using the CLSI M27-A3 document showed a wide range of MIC values (0.015-4 mg/L), with micafungin being the most potent in vitro inhibitor followed by anidulafungin and caspofungin (MIC geometric mean of 0.68, 0.74 and 0.87 mg/L, respectively). C. metapsilosis was the most susceptible species of the complex to anidulafungin and micafungin in vitro (MIC(50) for anidulafungin and micafungin: 0.06 mg/L), while there were no differences between C. parapsilosis sensu lato spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…17,31 According to this study C. parapsilosis isolates showed intermediate susceptibility to micafungin, corroborating previous findings that suggest a decreased susceptibility in C. parapsilosis. 3,12,17 The results of the present study show that the MIC values for amphotericin B among the three species of the Parapsilosis complex were similar. However, Lockhart et al 17 observed higher MIC values for C. parapsilosis.…”
Section: Discussionsupporting
confidence: 57%
“…17,31 According to this study C. parapsilosis isolates showed intermediate susceptibility to micafungin, corroborating previous findings that suggest a decreased susceptibility in C. parapsilosis. 3,12,17 The results of the present study show that the MIC values for amphotericin B among the three species of the Parapsilosis complex were similar. However, Lockhart et al 17 observed higher MIC values for C. parapsilosis.…”
Section: Discussionsupporting
confidence: 57%
“…Recent works have described a functional point mutation in the glucan synthase (FKS) gene of the C. parapsilosis complex species, which may explain this observation (46) (47) . FKS gene mutations have been shown to be associated with resistance to CAS, as demonstrated by increases in MICs in mutant isolates compared with those of wild-type isolates (48) (49) (50) . In summary, our study reported the first molecular identifi cation of C. parapsilosis complex species in State of Goiás, Brazil.…”
Section: In Vitro Susceptibility Testingmentioning
confidence: 99%
“…If Candida albicans remains the most frequent bloodstream fungal pathogen, but non-albicans species are increasing and are associated with variable susceptibility profiles to antifungal drugs (5). Recently, new cryptic Candida species were described (i.e., C. metapsilosis and C. orthopsilosis in the C. parapsilosis complex or C. nivariensis and C. bracarensis in the C. glabrata complex), species that conventional phenotypic identification methods cannot identify (6,7). Additionally, invasive infections due to the less frequent and naturally resistant to echinocandins species of the genera Cryptococcus, Trichosporon, Malassezia, and Rhodotorula have been observed (8).…”
mentioning
confidence: 99%